Personal Tutoring Scheme: Expectations, Perceptions and Factors Affecting Students’ Engagement - Calabrese, Gianpiero; Leadbitter, Debbie-Leigh M; Trindade, Neusa Do Sacramento Menezes Da; Jeyabalan, Ashveini; Dolton, Debbie; ElShaer, Amr (Frontiers in Education, 2022)
An effective Personal Tutoring Scheme is a crucial part of the strategy to support students’ progression and success rates in Higher Education institutions. This study investigated students’ expectations and perceptions of the Personal Tutoring Scheme in a post-1992 university in the UK. Data collection was achieved through a survey completed by 1078 students from all Faculties and was used to assess trends and factors affecting students’ expectations and perceptions of the Personal Tutoring Scheme. Results indicated that there is a gap between students’ expectations and perceptions, but that in comparison to previous literature this gap seems to be reducing. Unsurprisingly, frequency and regularity of meetings are linked with the development of a relationship with the Personal Tutor and a higher level of satisfaction. Higher Education institutions still have further work to do to close the gap between students’ expectations and perceptions; however, the results of this study indicate that this work is currently being undertaken.